Interpass rolling of Ti-6Al-4V wire + arc additively manufactured features for microstructural refinement - McAndrew, Anthony R.; Alvarez Rosales, Marta; Colegrove, Paul A.; Hönnige, Jan Roman; Ho, Alistair; Fayolle, Romain; Eyitayo, Kamal; Stan, Ioan; Sukrongpang, Punyawee; Crochemore, Antoine; Pinter, Zsolt (Elsevier, 2018)
In-process deformation methods such as rolling can be used to refine the large columnar grains that form when wire + arc additively manufacturing (WAAM) titanium alloys. Due to the laterally restrained geometry, application to thick walls and intersecting features required the development of a new ‘inverted profile’ roller. A larger radii roller increased the extent of the recrystallised area, providing a more uniform grain size, and higher loads increased the amount of refinement. Electron backscatter diffraction showed that the majority of the strain is generated toward the edges of the rolled groove, up to 3 mm below the rolled surface. These results will help facilitate future optimisation of the rolling process and industrialisation of WAAM for large-scale titanium components.
Keywords: Additive manufacturing; 3D printing; Deformation; EBSD; Rolling; Titanium